P46 | ANALYSIS OF AQUAPORIN-2 MUTANT MICE (European Journal of Histochemistry)
Aquaporin-2 (AQP2), a membrane water channel protein in kidney collecting duct cells, is necessary for urine concentration regulated by vasopressin (VP). AQP2 traffics to the apical membrane from intracellular vesicles, which is regulated by the phosphorylation and dephosphorylation of Ser256, Ser261, Ser264, and Ser269 of AQP2 caused by VP. Among them, Ser256 is critical for VP-induced urine concentration because S256L mice exhibit severe polyuria1. We focused on Ser269 and demonstrated that it is rapidly phosphorylated upon VP injection in rats2. To investigate the significance of Ser269 in AQP2 trafficking and urine concentration, we generated mutant mice using genome editing. In the process, we unexpectedly obtained AQP2.p.R252_V257del; S269D mutant mice. Despite lacking S256, these mice did not become polyuric. We analyzed the detailed phenotypes of this mutant. The osmolality of urine collected at any time in the morning, the 24-hour urine volume, and the 24-h water intake were not significantly different from those in wild-type mice. Then, we analyzed the immunolocalization of mutated AQP2 in the control state and after the administration of VP receptor agonist dDAVP or its antagonist OPC-31260. In wild-type mice, AQP2 localizes to the intracellular vesicles both in control state and after OPC-31260 administration, and it highly accumulates on the apical membrane after dDAVP administration. In mutant mice, mutated AQP2 localizes to some extent at the apical membrane, even in control. Neither dDAVPnor OPC-31260-administration changed the extent of apical localization of mutated AQP2. We then analyzed urine osmolality after oral water gavage and found that the mutant mice were unable to dilute their urine. These results suggest that the S269D mutation enables the accumulation of AQP2 on the apical membrane and rescues mice from polyuria, likely caused by the S256 deletion. On the other hand, uncontrolled accumulation of the mutated AQP2 on the apical membrane hampers urine dilution, even in cases of overhydration.